"all the appearances of being innovative": New Zealand architecture in the 1970s - McCarthy, Christine (Architectural History Aotearoa, 2022)
Mike Austin’s seemingly faint praise, in a 1974 review of a medium-density housing development, that the architecture had "all the appearances of being innovative," is echoed in Douglas lloyd Jenkins’ observation that: "Although the 1970s projected an aura of pioneering individualism, the image disguised a high degree of conformity." The decade’s anxious commencement, with the imminent threat of the European Economic Community (EEC) undermining our economic relationship with "Mother Britain," was perhaps symptomatic of a risqué appearance being only skin deep. Our historic access to Britain’s market to sell butter and cheese was eventually secured in the Luxembourg agreement, which temporarily retained New Zealand trade, but with reducing quotas, as a mechanism to gradually wean New Zealand’s financial dependency on exports to Britain.